Asuhan Keperawatan pada An. I dengan Gangguan Sistem Hematologi: Talasemia di Ruang Anggrek 2 RSUD dr. Soeselo Kabupaten Tegal - Nilna Permatasari; Esti Nur Janah; Tati Karyawati (Jurnal Anestesi, 2024)
Non-communicable diseases (NCDs) are diseases that are not caused by infection with microorganisms such as protozoa, bacteria, fungi or viruses. One example of a NCD is thalassaemia, which has strong genetic factors and an increasing incidence. Children who have parents or family members with thalassaemia have a higher risk of developing the disease. To establish basic assessment data, nurses will use the results of interviews, physical examinations, observations, and laboratory tests. Based on the results of the assessment conducted on An.I with thalassemia, three nursing diagnoses were found, namely ineffective peripheral perfusion associated with decreased haemoglobin concentration, fatigue associated with physiological conditions (anaemia), and knowledge deficit associated with lack of exposure to information. After evaluation, the problem of knowledge deficit was successfully resolved on the first day, while on the second day the problems of ineffective peripheral perfusion and fatigue were also resolved.